A protocol combining breath testing and ex vivo fermentations to study the human gut microbiome - Payling L; Roy NC; Fraser K; Loveday SM; Sims IM; Janssen PH; Hill SJ; Raymond LG; McNabb WC (Elsevier Inc, 2021)
This protocol describes the application of breath testing and ex vivo fermentations to study the association between breath methane and the composition and functionality of the gut microbiome. The protocol provides a useful systems biology approach for studying the gut microbiome in humans, which combines standardized methods in human breath testing and fecal sampling. The model described is accessible and easy to repeat, but its relative simplicity means that it can deviate from human physiological conditions.
Keywords: Cell Culture; Clinical Protocol; Genomics; Breath Tests; Feces; Gastrointestinal Microbiome; Humans